PENGEMBANGAN SELF NANO EMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) EKSTRAK DAUN SENGGUGU (Clerodendron serratum [L.]Spr.) - Erna Kusumawati; Iis Wahyuningsih; Nur Khasnah (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
Senggugu leaf (Cloredendrom serratum[L.]Spr.) is one of the natural ingredients that has a pharmacological effect in overcoming cancer since it contains flavonoid componds that prevents the development of cancer cells. However, the application of senggugu leaf extract through oral is not acceptable. Therefore, it requires the development of SNEDDS (Self- Nanoemulsifying Drug Delevery Sytem). Objectives: This study aims to formulate SNEDDS of senggugu leaf extract by using tween 80 surfactant and PEG 400 cosurfactane and Virgin Coconut Oil Phase in order for the optimal SNEDDS character to be obtained. Before making the DX 12 formula, a formula trial was made to determine the lower an upper values of each component. After that, a formula was made bases on the DX12. In order to make the optimal formula characterization, it is carried out of the optimal formula of SNEDDS, including particle size, zeta potential, and nanoemulsion stability in the artificial digestive system for 4 hours. The optimal characteristics that have been obtained has a transmitance percentage of 97,99±0,39 % within the emulsification time of 23,57 ±1,06 seconds, a droplet size of 12,5 ±0,436 nm, a polidispersity index of 0,320±0,005, a zeta potensial value of -30,6 ± 0,3 mV, and a stable nanoemulsion formed in the artifical disgetive tract. The results showed that the proportion of VCO 10,55%, tween 68%, and 21,45% PEG400 and 200 mg/mL extract was able to form a good formula for senggugu leaf extract SNEDDS.